Adult literacy facilitators’ job satisfaction in Nigeria and South Africa (2021)
This study reported a survey conducted to assess the job satisfaction level among adult literacy facilitators in Nigeria and South Africa. The study adopted a quantitative approach and data was collected from eighty-six (86) adult literacy facilitators (Nigeria-50 and South Africa-36) randomly selected from Oyo State, Nigeria and King Cetshwayo District, KwaZulu-Natal province, South Africa. A structured questionnaire validated by experts and pilot-tested among primary School teachers serves as the research instrument. Data collected from the study were analysed using frequency count, simple percentages, mean, multiple regression analysis and T-test. Results revealed that adult literacy facilitators' job satisfaction level in the two countries is on average. Provision of a positive working environment in terms of improvement in the infrastructural facilities in the literacy centre was ranked first amongst others as ways to improve the job satisfaction of literacy facilitators. There was, however, no statistical difference in job satisfaction among literacy facilitators in Nigeria and South Africa. Therefore, it was concluded that conscious effort must be made at mapping out strategies to improve literacy facilitators’ job satisfaction to enhance adult literacy delivery in the two countries